The “3D Versascrew”: An Innovative Approach for Management of Bilateral Cleft Lip and Palate Case - M. V. Ashith; NS Suma; K. Mithun; Dhruv Ahuja (Case Reports in Dentistry)
The purpose behind the innovation of modified nasoalveolar moulding appliance was to achieve simultaneous anteroposterior and transverse correction in bilateral cleft cases with minimal vomeroid bending. This paper presents a 3D Versascrew appliance that has been used for presurgical nasoalveolar moulding in a 15-day-old neonate with bilateral cleft. Treatment was initiated at 30 days and continued for 90 days following which mild expansion of posterior maxilla with establishment of arch continuity and concomitant improvement in nasal morphology was achieved towards the end.